Hippocampal subfield volumetric changes after radiotherapy for brain metastases - Holikova, Klara; Selingerova, Iveta; Pospisil, Petr; Bulik, Martin; Hynkova, Ludmila; Kolouskova, Ivana; Hnidakova, Lucie; Burkon, Petr; Slavik, Marek; Sana, Jiri; Holecek, Tomas; Vanicek, Jiri; et al. (Neuro-oncology advances, 2024)
BACKGROUND: Changes in the hippocampus after brain metastases radiotherapy can significantly impact neurocognitive functions. Numerous studies document hippocampal atrophy correlating with the radiation dose. This study aims to elucidate volumetric changes in patients undergoing whole-brain radiotherapy (WBRT) or targeted stereotactic radiotherapy (SRT) and to explore volumetric changes in the individual subregions of the hippocampus. METHOD: Ten patients indicated to WBRT and 18 to SRT underwent brain magnetic resonance before radiotherapy and after 4 months. A structural T1-weighted sequence was used for volumetric analysis, and the software FreeSurfer was employed as the tool for the volumetry evaluation of 19 individual hippocampal subregions. RESULTS: The volume of the whole hippocampus, segmented by the software, was larger than the volume outlined by the radiation oncologist. No significant differences in volume changes were observed in the right hippocampus. In the left hippocampus, the only subregion with a smaller volume after WBRT was the granular cells and molecular layers of the dentate gyrus (GC-ML-DG) region (median change -5 mm3, median volume 137 vs. 135 mm3; P = .027), the region of the presumed location of neuronal progenitors. CONCLUSIONS: Our study enriches the theory that the loss of neural stem cells is involved in cognitive decline after radiotherapy, contributes to the understanding of cognitive impairment, and advocates for the need for SRT whenever possible to preserve cognitive functions in patients undergoing brain radiotherapy.
Keywords: volumetry; metastasis; hippocampus; radiotherapy; brain